2014
DOI: 10.1175/mwr-d-12-00252.1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Automated Methods of Front Recognition for Climate Studies: A Case Study in Southwest Western Australia

Abstract: The identification of extratropical fronts in reanalyses and climate models is an important climate diagnostic that aids dynamical understanding and model verification. This study compares six frontal identification methods that are applied to June and July reanalysis data over the Central Wheatbelt of southwest Western Australia for . Much of the winter rainfall over this region originates from frontal systems. Five of the methods use automated algorithms. These make use of different approaches, based on shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 43 publications
3
74
0
3
Order By: Relevance
“…Frontal systems are very important for rainfall in southern Australia (Berry et al, 2011;Simmonds et al, 2012) particularly in the southeast in autumn (Catto et al, 2012) and the southwest in winter, where they have been found to be declining in number (Hope et al, 2014). Fronts in an example GCM, ACCESS1.3, tend to be well represented in their frequency and the proportion of precipitation associated with them (Catto et al, 2013), although the intensity of that precipitation is underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Frontal systems are very important for rainfall in southern Australia (Berry et al, 2011;Simmonds et al, 2012) particularly in the southeast in autumn (Catto et al, 2012) and the southwest in winter, where they have been found to be declining in number (Hope et al, 2014). Fronts in an example GCM, ACCESS1.3, tend to be well represented in their frequency and the proportion of precipitation associated with them (Catto et al, 2013), although the intensity of that precipitation is underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…A strong inverse relationship has been found between coastal SWA rainfall and the MSLP over the region (Allan and Haylock 1993;Ansell et al 2000;Li et al 2005), indicating the role of large-scale circulation pattern in controlling the rainfall. In particular, the decline in winter rainfall has been associated with the reduced frequency of front-like low pressure systems over the region (Hope et al 2006;Alexander et al 2010) and the increases in both station MSLP over SWA and sea surface temperature (SST) over the southern Indian Ocean . For example, Risbey et al (2013) found that the reduction in coastal JJA rainfall during 1985-2009 is mostly associated with the frontal systems.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a decrease in the number of low pressure systems, the mean annual frequency of fronts in the region, as deduced from several reanalyses, has increased during 1989-2009 (Berry et al 2011a). It is likely that these conflicting conclusions can be attributed to the different methods used to identify and classify rain-bearing synoptic systems such as fronts, troughs, and cutoff lows (Hope et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations